2018
DOI: 10.3892/mmr.2018.9274
|View full text |Cite
|
Sign up to set email alerts
|

Lycium�barbarum polysaccharides protect human trophoblast HTR8/SVneo cells from hydrogen peroxide‑induced oxidative stress and apoptosis

Abstract: Pregnancy complications are associated with abnormal cytotrophoblast differentiation and invasion. Hydrogen peroxide (H2O2) is an important mediator of oxidative ischemia/reperfusion stress in the placenta. Lycium barbarum polysaccharides (LBP) have been demonstrated to counteract oxidative free radicals. The effects of LBP in trophoblast HTR8/SVneo cells injured with H2O2 were examined. A cell counting kit-8 assay was performed to detect the effect of LBP at different concentrations on the proliferative abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
(42 reference statements)
1
11
0
Order By: Relevance
“…It is well established that H2O2 could be used to stimulate oxidative stress in vitro [30][31][32]. In the present study, we found that treatment with 400 μM H2O2 resulted in decreased cell viability in HTR8/SVneo cells, which is consistent with a previous study [1]. Curcumin has been reported to be toxic at a high dose, while it exerts a strong antioxidant effect at a low dose [23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well established that H2O2 could be used to stimulate oxidative stress in vitro [30][31][32]. In the present study, we found that treatment with 400 μM H2O2 resulted in decreased cell viability in HTR8/SVneo cells, which is consistent with a previous study [1]. Curcumin has been reported to be toxic at a high dose, while it exerts a strong antioxidant effect at a low dose [23].…”
Section: Discussionsupporting
confidence: 92%
“…Intrauterine growth retardation (IUGR) and preeclampsia (PE) are detrimental pregnancy complications that could cause significant increased perinatal morbidity and mortality [1]. Normal placental development during early pregnancy depends entirely on the differentiation, proliferation, and invasion of trophoblast cells [2].…”
Section: Introductionmentioning
confidence: 99%
“…The peroxidative environment was simulated in our experiments by using hydrogen peroxide at similar concentrations as those previously used in the same cell lines [37,60], since it is physiologically produced in maternal circulation and its levels are increased in preeclamptic patients in the early stages of pregnancy [61]. Also, the concentration of hydrogen peroxide was similar to the one that has been shown to cause senescence in hUSMCs [60].…”
Section: Discussionmentioning
confidence: 99%
“…The used concentrations of hCG and estradiol were in the range of plasma values found in humans [35,36]. Also hydrogen peroxide was used at a concentration similar to the one previously used in the same cell lines [37]. The culture medium from hUMSCs was also collected and used for co-stimulation experiments after centrifugation and filtration.…”
Section: Methodsmentioning
confidence: 99%
“…Since sPIF modulated inflammation during pregnancy (Fig 1) [20], we decided to test sPIF in challenged placental cells next. We chose to test pro-inflammatory (IL-6 and NLRP4) and proapoptotic (Bad and Bax) genes as they contribute to pregnancy complications such as PTB [5,20,51,52]. We detected moderate changes after sPIF-only treatment (Fig 2A and 2B; compare green to black bars).…”
Section: Synthetic Pif Reduces the Inflammatory Response (In-vivo)mentioning
confidence: 99%